Trusted platform module basics using TPM in embedded systems - Kinney, Steven (Embedded technology series)
Intended for embedded designers, this book provides a foundation on the TPM, helping designers take advantage of hardware security based on sound TCG standards. It covers the TPM basics, discussing the TPM Key Hierarchy and the Trusted Platform Module specification. It also includes an accompanying CD-ROM that contains source code.